Chronic trans-astaxanthin treatment exerts antihyperalgesic effect and corrects co-morbid depressive like behaviors in mice with chronic pain. (1st January 2018) - Jiang, Xi; Yan, Qizhi; Liu, Fuhe; Jing, Changfeng; Ding, Lianshu; Zhang, Lijin; Pang, Cong
Highlights: Trans-astaxanthin prevented CCI-induced allodynia and co-morbid depressive-like behavior. Effects of trans-astaxanthin on allodynia and co-morbid depression involves the serotonergic system. Trans-astaxanthin prevented CCI-induced pro-inflammatory cytokine increase in hippocampus and spinal cord. Abstract: Patients suffering from chronic neuropathic pain are at high risk of co-morbid depression, which burdens healthcare. Trans-astaxanthin has been shown in our previous studies to exert antidepressant-like effect. This work aimed to investigate the effects of trans-astaxanthin on pain-related depressive-like behaviors in mice and explored the mechanism(s). Chronic constriction injury (CCI) model was used in this research. Chronic pain was evaluated by thermal hyperalgesia in Hargreaves test and mechanical allodynia in von Frey test, depressive-like behaviors were evaluated by immobility time in forced swim test and tail suspension test. Chronic trans-astaxanthin treatment ameliorated mechanical allodynia and thermal hyperalgesia, as well as decreasing immobility time in forced swim test and tail suspension test in CCI mice, and these actions were abolished by co-treatment with P-Chlorophenylalanine (PCPA). Subsequent study indicated that indoleamine 2, 3-dioxygenase (IDO) expression increased after CCI surgery in hippocampus and spinal cord, accompanied by increase of kynurenine (KYN)/tryptophan (TRY) ratio, decrease of serotonin (5-HT)/TRY ratio and decrease of 5-HT/5-HIAA ratio. The above results affected by CCI surgery were reversed by trans-astaxanthin treatment. Moreover, trans-astaxanthin at 80 mg/kg was demonstrated to effectively antagonize IL-1β, IL-6 and TNF-α expression in hippocampus and spinal cord of CCI mice. Taken together, chronic trans -astaxanthin administration exerts therapeutic effects on thermal hyperalgesia and co-morbid depressive-like behaviors in CCI mice. These effects of trans-astaxanthin involves the serotonergic system, and also may be owing to its potent anti-inflammatory property.